Modeling the imaging chain of digital cameras - Fiete, Robert D. (SPIE, 2010)
The process by which an image is formed, processed, and displayed can be conceptualized as a chain of physical events called the imaging chain. By mathematically modeling the imaging chain, we can gain insight into the relationship between the camera design parameters and the resulting image quality. The mathematical models can also be used to optimize and assess the design of a camera for specific applications before expenditures are committed to building hardware. Modeling the Imaging Chain of Digital Cameras teaches the key elements of the end-to-end imaging chain for digital camera systems and describes how elements of the imaging chain are mathematically modeled using the basics of linear systems mathematics and Fourier transforms. The emphasis is on general digital cameras designed to image incoherent light in the visible imaging spectrum. The reader will learn how digital camera design parameters are related to the elements of the imaging chain and how they influence the resulting image quality. The book also discusses the use of imaging chain models to simulate images from different digital camera designs for image quality evaluations.
"SPIE Digital Library."--Website.
Keywords: Photographic optics -- Mathematics.; Digital cameras -- Mathematical models.; Photography -- Digital techniques.; elektronické knihy; electronic books